2017
DOI: 10.1016/j.joi.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Global science discussed in local altmetrics: Weibo and its comparison with Twitter

Abstract: a b s t r a c tLocal altmetrics is currently an integral part of the altmetrics landscape. This paper aims to investigate the characteristics of microblog altmetrics of the Chinese microblog platform, Weibo, to shed light on cultural differences and draw attention to local altmetrics in developing countries. The analysis is based on 4.4 million records provided by Altmetric.com. Data collected are from March 2014 to July 2015. It is found that Weibo users discuss global science, more actively compared with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…Our findings about Twitter may be due to the fact that Twitter is a real-time microblog network. Consequently, an article might be tweeted within few hours after publication (Yu et al 2017). Furthermore, Gold OA publications might be immediately available through preprint repositories, before the official release.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings about Twitter may be due to the fact that Twitter is a real-time microblog network. Consequently, an article might be tweeted within few hours after publication (Yu et al 2017). Furthermore, Gold OA publications might be immediately available through preprint repositories, before the official release.…”
Section: Discussionmentioning
confidence: 99%
“…Ortega (2018) made a comparison of temporal distribution at the month time interval among citations, views, downloads, Mendeley readership, tweets, and blog mentions recorded by PlumX, and concluded that tweets and blog mentions are the quickest available metrics. Yu et al (2017) found that Twitter and Weibo are more immediate than citations, however they also suggested that not all altmetric data sources have the same degree of immediacy.…”
Section: Accumulation Patterns and Immediacy Measurement Of Altmetricmentioning
confidence: 99%
“…Este género de ferramentas Yuxiong Zhang e António Moreira Interfaces da Educ., Paranaíba, v.10, n.28, p.226 à 270, 2019 ISSN 2177-7691 233 permite publicar mensagens de pequeno tamanho, partilhando-as na comunidade criada pelos próprios utilizadores (BORAU et al, 2009). E isto, com efeito, pode ser uma maneira mais fácil e relaxante para iniciar a produção de conteúdo na língua-alvo, fomentando um sentido de comunidade dentro e fora da sala de aula (RUIPÉREZ GARCÍA et al, 2011, LOMICKA & LORD, 2012 Paranaíba, v.10, n.28, p.226 à 270, 2019 ISSN 2177-7691 234 nos posts (YU et al, 2017). É considerado como um fórum virtual mais público que oferece um espaço para a autoapresentação e interação com os indivíduos com interesses idênticos (SHU et al, 2017;HOU et al, 2018 Educ., Paranaíba, v.10, n.28, p.226 à 270, 2019 ISSN 2177-7691 235 disponibilizando contextos casuais da aprendizagem de língua com conversas abertas (LANTZ-ANDERSSON, 2017).…”
Section: Interfaces Daunclassified